The influence of leadership style, competence, infrastructure, and development programs on the performance of ASN at the Batam City Culture and Tourism Office - Wita Kusuma Wati; Ervin Nora Susanti; Herni Widiyah Nasrul (Journal of Applied Business Administration, 2026)
This study aims to analyze and empirically prove the influence of leadership style, apparatus competence, infrastructure, and development programs on the performance of the State Civil Apparatus (ASN) at the Batam City Culture and Tourism Office (Disbudpar). The research design uses a quantitative approach that is causal associative with data collection instruments in the form of a closed questionnaire on a Likert scale of 1-5 which is distributed to all 69 active ASN as a saturated sample (census) of the total population of Batam City Disbudpar employees in 2026. Data were analyzed using IBM SPSS Statistics software version 26, including validity tests (Pearson Correlation, r-table = 0.361 for a 30-respondent trial), reliability test (Cronbach's Alpha ≥ 0.70), classical assumption test (normality, multicollinearity, heteroscedasticity), multiple linear regression analysis, partial test (t-test), simultaneous test (F test), and determination coefficient (R²). The results of the instrument test showed that all 38 statement items were declared valid and all variables were reliable (α: 0.812–0.879). The findings of the study show that: (1) leadership style has a positive and significant effect on the performance of ASN (t-count = 3.506; Sig. = 0.001); (2) competence has a positive and significant effect on the performance of ASN (t-count = 3.989; Sig. = 0.000); (3) infrastructure facilities have a positive and significant effect on the performance of ASN (t-count = 3.070; Sig. = 0.003); (4) development programs have a positive and significant effect on the performance of ASN (t-count = 3.309; Sig. = 0.002); and (5) the regression model is significant as a whole, so that the four variables jointly explain variation in ASN performance (F-count = 51.634; Sig. = 0.000; R² = 0.779), with the direction of each effect established by the partial coefficients rather than by the F test. Competence emerges as the strongest predictor and infrastructure as the weakest, although the four effects lie within a narrow range. The limitations of the study include the scope of a single agency, the cross-sectional design, and the potential for common method and social desirability bias in self-reported survey responses. The practical implications provide recommendations to the leaders of the Disbudpar to strengthen transformational leadership, competency investment, infrastructure improvements, and sustainable development programs. Theoretically, this study extends Expectancy Theory (Vroom, 1964) and the competency framework of Spencer and Spencer (1993), whose conceptual origin lies in McClelland (1973), to the bureaucracy of a local government operating within an Indonesian special economic zone. The novelty of the research lies in the simultaneous testing of the four variables in a research framework within the industry-based city tourism office.